DIGITAL MARKETING ASSISTANCE AS AN EFFORT TO IMPROVE BUSINESS PERFORMANCE IN RINGINANOM VILLAGE - M Haris Al Ayubi; Yeny Fitriyani (khidmatan, 2023)
This Community Service activity aims to provide training on the application of digital marketing as a marketing strategy for Micro, Small and Medium Enterprises (MSMEs) so that it can produce marketing that can reach the wider community, increase the number of consumers and attract buyer interest. MSME business actors in Ringinanom village need technology-based business development to be able to compete with their competitors. Therefore, outreach and training need to be carried out to provide knowledge and understanding of the importance of digital marketing for their business. There are two methods used in assisting MSME businesses in digital marketing, namely workshops and direct practice. Introduction to digital marketing as an introduction to this program as well as the benefits obtained from using digital marketing. In this training, we utilize an application in the Play Store Application, namely the Photoroom Application. Business actors who take part in this training are expected to be able to implement the results of the training and discuss with other business actors and the surrounding community. Advice that can be given in creating content marketing is to add interesting captions and hashtags that are easy to follow so that products are easy to find.